ZOOPLANKTON COMMUNITY STRUCTURE AT MAJAKERTA ESTUARY AND ITS SURROUNDING WATERS, INDRAMAYU REGENCY, WEST JAVA PROVINCE - Happy Widyarini; Niken T.M. Pratiwi; . Sulistiono (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Majakerta estuary and its surrounding waters have a high potential fishery resource which is commonly utilized by the community around the area. Fluctuation of physical and chemical parameters of the waters and fishery activities around the estuary can influence the existence of  zooplankton. This study was conducted from December 2014 to May 2015. Samples of the zooplankton were collected monthly at four stations (consisted of sea, river and estuary areas). Based on the study, zooplankton in the  Majakerta estuary and its surrounding waters consisted of six classes; i.e. Protozoa (11 genera), Crustaceae (4 genera, 1 nauplius stadia), and Rotifera (4 genera). A higher abundance was found at the sea (29025 ind./m3), while a lower  abundance was at the river and estuary (7147 ind./m3 dan 7582 ind./m3).  Based on the zooplankton diversity index, it can be inferred that the value was relatively low. There were two habitat groups, namely Station Group 1 (Station 1 and  2; river and estuary) and Station Group 2 (Station  3 and 4; sea) with influencing parameters such as  transparency, pH, and salinity.  Keywords: estuary, Majakerta, zooplankton, community structure